1989
DOI: 10.2134/jeq1989.00472425001800020006x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sewage Sludge and Other Amendments to Coal Refuse Material: I. Effects on Chemical Composition

Abstract: The effects of sewage sludge, lime, and gypsum on the chemical composition of coal refuse material were examined at a Fulton County, IL, land reclamation site. Treatments consisted of a control, 542 dry Mg ha−1 anaerobically digested sewage sludge, 89.6 Mg ha−1 lime, 112 Mg ha−1 gypsum, and combinations of these amendments. Analysis of coal refuse material (0–15 cm) from 1976 to 1981 showed that the sewage sludge + lime treatment was the most effective in maintaining the refuse pH, and in reducing water‐solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Biosolids have been similarly blended with lime, other alkali and various salts after biosolid production for improving alkalinity and soil productivity. Lime and gypsum treated anaerobically biosolids post production were used by Pietz et al [164,165] for revegetation of acidic coal refuse material. It was found that the lime + biosolid and gypsum + biosolid treatments reduced soil acidity and dissolved Al and increased plant productivity compared to control and individual amendments.…”
Section: Methodsmentioning
confidence: 99%
“…Biosolids have been similarly blended with lime, other alkali and various salts after biosolid production for improving alkalinity and soil productivity. Lime and gypsum treated anaerobically biosolids post production were used by Pietz et al [164,165] for revegetation of acidic coal refuse material. It was found that the lime + biosolid and gypsum + biosolid treatments reduced soil acidity and dissolved Al and increased plant productivity compared to control and individual amendments.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction of organic matter with soils is enhanced by Ca 2þ , resulting in (i) the additional pH buffering capacity of Ca 2þ present in FA, (ii) its contribution to the flocculation of soil particles and stabilization of soil structure through cation bridging and (iii) sorption of organic matter to mineral surfaces to create a more reactive environment for water, air and nutrient interactions in the soil (Palumbo et al, 2004). Sewage sludge and other mineral amendments, such as lime and gypsum, added along with FA, maintained optimum pH, altered water-soluble organic carbon and EC, and released N, P and K for assimilation by plants during re-vegetation of soil and mine spoil (Pietz et al, 1989).…”
Section: Treatmentmentioning
confidence: 99%
“…FA does not inhibit microbial activity and respiration in the case of its application of organic materials, such as swine manure (Vincini et al, 1994); in fact, an improvement in the microbial community content in degraded subsoil due to the amendment with FA has been observed (Schutter & Fuhrmann, 2001). The addition of biosolids and other amendments, including humic acid and fertilizers, to FA has been effective in maintaining the pH of the soil, improving the water-soluble OC content and electrical conductivity, and releasing N, P, and K for assimilation by plants during revegetation of soil (Martens & Beahm, 1976;Pietz et al, 1989). Although the metals content in the plant species grown was not determined in this study, it is possible that the reduction in toxicity of certain metals from FA, along with an increase in the supply of nutrients, is also likely due to the addition of organic amendments (Chu & Poon, 1999;Wong, 1995).…”
Section: Effect Of Amendmentsmentioning
confidence: 99%